Contribution of SARS-CoV-2 Accessory Proteins to Viral Pathogenicity in K18 Human ACE2 Transgenic Mice - Silvas, Jesus A.; Vasquez, Desarey Morales; Park, Jun-Gyu; Chiem, Kevin; Allué-Guardia, Anna; Garcia-Vilanova, Andreu; Platt, Roy Neal; Miorin, Lisa; Kehrer, Thomas; Cupic, Anastasija; Gonzalez-Reiche, Ana S.; Bakel, Harm van; et al. (Journal of virology, 2021)
Despite great efforts put forward worldwide to combat the current coronavirus disease 2019 (COVID-19) pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to be a human health and socioeconomic threat. Insights into the pathogenesis of SARS-CoV-2 and the contribution of viral proteins to disease outcome remain elusive. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the viral pathogen responsible for the current coronavirus disease 2019 (COVID-19) pandemic. As of 19 May 2021, John Hopkins University’s COVID-19 tracking platform reported 3.3 million deaths associated with SARS-CoV-2 infection. Currently, the World Health Organization has granted emergency use listing (EUL) to six COVID-19 vaccine candidates. However, much of the pathogenesis observed during SARS-CoV-2 infection remains elusive. To gain insight into the contribution of individual accessory open reading frame (ORF) proteins in SARS-CoV-2 pathogenesis, we used our recently described reverse-genetics system approach to successfully engineer recombinant SARS-CoV-2 (rSARS-CoV-2) constructs; we removed individual viral ORF3a, −6, −7a, −7b, and −8 proteins from them, and we characterized the resulting recombinant viruses in vitro and in vivo . Our results indicate differences in plaque morphology, with ORF-deficient (ΔORF) viruses producing smaller plaques than those of the wild type (rSARS-CoV-2/WT). However, growth kinetics of ΔORF viruses were like those of rSARS-CoV-2/WT. Interestingly, infection of K18 human angiotensin-converting enzyme 2 (hACE2) transgenic mice with the ΔORF rSARS-CoV-2s identified ORF3a and ORF6 as the major contributors of viral pathogenesis, while ΔORF7a, ΔORF7b, and ΔORF8 rSARS-CoV-2s induced pathology comparable to that of rSARS-CoV-2/WT. This study demonstrates the robustness of our reverse-genetics system to generate rSARS-CoV-2 constructs and the major role for ORF3a and ORF6 in viral pathogenesis, providing important information for the generation of attenuated forms of SARS-CoV-2 for their implementation as live attenuated vaccines for the treatment of SARS-CoV-2 infection and associated COVID-19. IMPORTANCE Despite great efforts put forward worldwide to combat the current coronavirus disease 2019 (COVID-19) pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to be a human health and socioeconomic threat. Insights into the pathogenesis of SARS-CoV-2 and the contribution of viral proteins to disease outcome remain elusive. Our study aims (i) to determine the contribution of SARS-CoV-2 accessory open reading frame (ORF) proteins to viral pathogenesis and disease outcome and (ii) to develop a synergistic platform combining our robust reverse-genetics system to generate recombinant SARS-CoV-2 constructs with a validated rodent model of infection and disease. We demonstrate that SARS-CoV-2 ORF3a and ORF6 contribute to lung pathology and ultimately disease outcome in K18 hACE2 transgenic mice, while ORF7a, ORF7b, and ORF8 have little impact on disease outcome. Moreover, our combinatory platform serves as a foundation for generating attenuated forms of the virus to develop live attenuated vaccines for the treatment of SARS-CoV-2.